Inovasi Pengolahan Ubi Jalar Dengan Pembuatan Kue Tarajju Dalam Program Pemberdayaan Masyarakat Desa Honai Lama II Kecamatan Wamena Kota - Inrianti Inrianti; Meri Berliana; Patras Pumuko; Erinus Mosip; Rudianto Tumanggor; Sumiyati Tuhuteru (Universitas Katolik Widya Karya Malang, 2023)
Empowerment is an effort to awaken the strength and potential of the community which is based on the local community through a participatory approach and learning together. The purpose of empowerment is the condition to be achieved either from a social change which becomes a more empowered society, has the power as well as the knowledge and ability to be able to better fulfill their life needs. Economic empowerment is said to be important because this empowerment will create increased welfare for the community. The aim of this sweet potato processing innovation is to increase the community's skills in processing sweet potatoes which are a staple food that is usually baked and boiled into a product that has economic value. The counseling activity was carried out using the Cooking Demo method, the community seemed very enthusiastic about following the process of making Tarajju cakes, this can be seen from the many people who asked and wanted to get a complete explanation of the process of processing sweet potatoes into cakes.